Pengaruh Kualitas Pelayanan terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen pada Bengkel Prima Sejahtera Pekanbaru - Fadhlan Maulana; Meyzi Heriyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of the automotive sector in Indonesia, especially on cars, has encouraged the growth of vehicle maintenance and repair service businesses. One of the workshops that is present to answer this need is Bengkel Prima Sejahtera on Jl. Sejahtera, Pekanbaru. This workshop always strives to provide the best quality of service to its consumers. The purpose of this study is to determine the direct and indirect influence of service quality (X) on consumer loyalty (Y) through consumer satisfaction (Z) at Bengkel Prima Sejahtera Pekanbaru. The research method is a quantitative method. This study shows (1) service quality directly has a positive and significant effect on consumer loyalty (2) service quality directly has a positive and significant effect on consumer satisfaction (3) consumer satisfaction directly has a positive and significant effect on consumer loyalty (4) service quality indirectly on consumer loyalty through consumer satisfaction has a positive and significant effect. This shows that good service quality will satisfy consumers so that it can increase consumer loyalty.